The efficacy and safety of platinum plus gemcitabine (PG) chemotherapy with or without molecular targeted agent (MTA) in first-line treatment of non-small cell lung cancer (NSCLC). Issue 50 (December 2016) - Yang, Jiaying; He, Jieyu; Yu, Miao; Li, Taishun; Luo, Li; Liu, Pei
Abstract: Background: Trials investigating the efficacy and safety of combining molecular targeted agent (MTA) with platinum–gemcitabine (PG) in first-line treatment of advanced non-small cell lung cancer (NSCLC) have shown inconsistent findings. This meta-analysis aimed to explore whether the addition of MTAs to PG in NSCLC could provide a survival benefit with a tolerable toxicity. Methods: Web of knowledge, PubMed, Ovid, Embase, and Cochrane Library were searched to identify relevant studies and extract data on overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and common grade 3 or 4 adverse events. Subgroup analyses were conducted on the basis of race and the type of MTA. Results: Twelve trials with a total of 6143 patients were included in this meta-analysis. Compared with PG chemotherapy, combination therapy of MTA with PG did not improve OS (hazard ratio [HR] = 0.96, 95% confidence interval [CI] = 0.90–1.01) but improved PFS (HR = 0.77, 95% CI = 0.66–0.89) and ORR (risk ratio [RR] = 1.33, 95% CI = 1.11–1.60). Subanalysis indicated that there was more incidence of grade 3 or 4 rash (RR = 11.20, 95% CI = 6.07–20.68), anemia (RR = 1.21, 95% CI = 1.01–1.46), diarrhea (RR = 2.62, 95% CI = 1.21–5.65), and anorexia (RR = 2.08, 95% CI = 1.12–3.88) in combining epidermal growth factor receptor targeted therapy group compared to PG group. An increased risk of grade 3 or 4 rash (RR = 5.08, 95% CI = 1.53–16.79), thrombocytopenia (RR = 1.50, 95% CI = 1.03–2.18), and hypertension (RR = 2.36, 95% CI = 1.05–5.32) was observed in sorafenib combination group. Conclusion: The combination of PG plus MTA was superior to PG alone in terms of PFS and ORR but not in OS. The combination chemotherapy also showed a higher frequency of grade 3 or higher toxic effects in patients with advanced NSCLC than PG chemotherapy. Abstract : Supplemental Digital Content is available in the text